2014
DOI: 10.1007/s10529-014-1638-7
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, homology modeling, and reaction mechanism analysis of a novel cis-epoxysuccinate hydrolase from Klebsiella sp.

Abstract: The gene encoding a novel cis-epoxysuccinate hydrolase, which hydrolyzes cis-epoxysuccinate to L (+)-tartaric acid, was cloned from Klebsiella sp. BK-58 and expressed in Escherichia coli. The ORF was 825 bp encoding a mature protein of 274 amino acids with a molecular mass of 30.1 kDa. Multiple sequence alignment showed that the enzyme belonged to the haloacid dehalogenase-like super family. Homology modeling and site-directed mutagenesis were performed to investigate the structural characteristics of the enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…We used classical directed evolution techniques to improve the ESH catalytic activity and the relative activity was significantly increased (230 %) by a single mutation, Phe10Gln. In addition, according to the sequence alignments for ESH (Cheng et al 2014a), we speculated that the point Phe10 may be an important catalytic site of the enzyme, which still needs specific research of protein crystal structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used classical directed evolution techniques to improve the ESH catalytic activity and the relative activity was significantly increased (230 %) by a single mutation, Phe10Gln. In addition, according to the sequence alignments for ESH (Cheng et al 2014a), we speculated that the point Phe10 may be an important catalytic site of the enzyme, which still needs specific research of protein crystal structures.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous reports (Cheng et al 2014a), ESH has an a/b hydrolase fold and nine conserved catalytic residues (Carr and Ollis 2009;Ollis et al 1992;Porter et al 2015). Therefore, we started from the six conserved sites (Thr52, Arg85, Asn165, Lys195, Tyr201 and Ala219) except for the highly conserved catalytic triad Asp48-His221-Asp224.…”
Section: Semi-saturation Mutagenesis For the 6 Conserved Sitesmentioning
confidence: 99%
“…BK-52 and CESH[L]s from Rhodococcus opacus , Nocardia tartaricans , and Klebsiella sp. BK-58, have also been sequenced and cloned [17,19,41,42,43]. The genes and the derived amino acid sequences of CESHs provided the basis for later studies of the recombinant expression, structure, and mechanisms as well as the protein engineering of CESHs.…”
Section: The History Of Cesh Studiesmentioning
confidence: 99%
“…Analyses of the amino acid sequences of CESHs indicated that CESH[D]s and CESH[L]s are completely different proteins [19]. Subsequent structural analysis and mechanism studies revealed that they have different structures and catalysis mechanisms [41,43,44,45]. In a recent study [46], we determined a high-resolution structure and elucidated detailed catalytic mechanisms for CESH[D], but these characteristics have not yet been reported for CESH[L].…”
Section: The History Of Cesh Studiesmentioning
confidence: 99%
See 1 more Smart Citation